MITgcm configuration and simulations for the test of the teardrop yield curve - Ringeisen, Damien; Losch, Martin; Tremblay, Bruno (Zenodo, 2022)
In this archive, there is: Two versions of MITgcm checkpoint 67z (https://doi.org/10.5281/zenodo.4968496) with modified sea ice packages. The changes are limited to the files "seaice_calc_viscosities.F": The first version with the teardrop and parabolic lens yield curve as described in Zhang and Rothrock (2005) (DOI:10.1029/2004JC002599). It is present in the file "MITgcm/seaice_calc_viscosities_original.F" and copied in "build_ori" folder in "sims" The second with new formulations of teardrop and parabolic lens yield curves (These are slightly modified from the one already present in MITgcm checkpoint 67z). The changes are in the file "MITgcm/pkg/seaice/seaice_calc_viscosities.F" and linked to the folder "build_fix" in "sims". A python "yield_curve.py" script used to compare both versions of the formulation with simulated deformation data. The configuration files for the uniaxial compression experiments that were used to compare both versions of MITgcm above. ("MITgcm/exps/" and all the "data*" and "gendata.py" files in the experiments folders) The results of the simulations performed with the versions above (folders "sims/run??") run11: new formulation of the teardrop yield curve - 5h - 10 outer loops run08l2: new formulation of the teardrop yield curve - 10 timesteps - 15000 outer loops run09: original formulation of the teardrop yield curve - 5h - 10 outer loops run09l2: original formulation of the teardrop yield curve - 10 timesteps - 15000 outer loops run10: elliptical yield curve - 5h - 10 outer loops run10l : elliptical yield curve - 10 timesteps - 15000 outer loops The scripts to plot and analyze the result, used for publication. plot_yc_comp.py to plot the results of simulations plot_data.py are utilities for plot_yc_comp.py plotresgmres.py is used to plot the numerical convergence of the simulations : This project has been supported by the Deutsche Forschungsgemeinschaft (DFG) through the International Research Training Group "Processes and impacts of climate change in the North Atlantic Ocean and the Canadian Arctic" (grant no. IRTG 1904 ArcTrain). : {"references": ["Zhang, J., & Rothrock, D. A. (2005). Effect of sea ice rheology in numerical investigations of climate.Journal of Geophysical Research: Oceans,110(C8), C08014. doi: 10.1029/2004JC002599"]}